2015
DOI: 10.1177/0363546515616237
|View full text |Cite
|
Sign up to set email alerts
|

Hip Muscle Strength Predicts Noncontact Anterior Cruciate Ligament Injury in Male and Female Athletes

Abstract: Background The role of lower extremity (LE) muscle strength for predicting traumatic knee injury in youth athletes is largely unknown. Aims The aim was to investigate the influence of LE muscle strength on traumatic knee injury in youth female and male athletes. Methods 225 athletes (40% females) from sport senior high schools in Sweden were included in this case-control study. The athletes recorded any traumatic knee injury that had occurred during their high-school period in a web-based injury form. A one re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
174
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(208 citation statements)
references
References 27 publications
5
174
2
4
Order By: Relevance
“…Potentially, this requires adequate hip girdle strength to maintain stability of the pelvis and trunk throughout the test. Although relationships have been reported between various components of lower-extremity and core strength and injury, [7][8][9] the relationship between hip strength and performance on the Y Balance Test has yet to be fully elucidated. [10][11][12] Only 2 studies to date have assessed correlations between the SEBT or Y Balance Test and hip strength.…”
mentioning
confidence: 99%
“…Potentially, this requires adequate hip girdle strength to maintain stability of the pelvis and trunk throughout the test. Although relationships have been reported between various components of lower-extremity and core strength and injury, [7][8][9] the relationship between hip strength and performance on the Y Balance Test has yet to be fully elucidated. [10][11][12] Only 2 studies to date have assessed correlations between the SEBT or Y Balance Test and hip strength.…”
mentioning
confidence: 99%
“…Though the database used for the present study did not contain information that would help identify the source of increased anterior asymmetry on the SEBT, such as ankle dorsiflexion range of motion or lower extremity muscle strength imbalances, previous research suggests that deficits in strength, flexibility, and neuromuscular control may influence injury risk. 14,18,26 To facilitate development of screening and training programs that effectively reduce injury risk, future research should aim to determine the underlying causes of increased anterior asymmetry. Sideto-side asymmetry normalized to limb length has been previously described in healthy Division I collegiate athletes, 27 but to the authors' knowledge, the present study is the first to associate these values with injury.…”
mentioning
confidence: 99%
“…Compared to males, females demonstrated lower strength in all directions except extension and greater flexion and IR ROM. Previous studies have also shown females exhibit significant lower hip muscle strength than males in both normal (Kemp, Schache, Makdissi, Sims, & Crossley, 2013) and athletic (Khayambashi, Ghoddosi, Straub, & Powers, 2016) populations, as well as in patients with chondrolabral pathology, 12-24 months post-surgery (Kemp, Schache, Makdissia, Pritchard, Sims et al, 2014d). Other studies have reported that populations of normal and active females demonstrate greater hip flexion (Beneck, Selkowitz, Janzen, Malecha, & Tiemeyer, 2018;Hallaçeli et al, 2014) and IR ROM (Hallaçeli et al, 2014; Moreno-PĂ©rez, Ayala, Fernandez-Fernandez, & Vera-Garcia, 2016) than males.…”
Section: Discussionmentioning
confidence: 93%